Occupational Safety Risk Management: A Planning Model to Optimise Resource Allocation - Application to the Western Australian Mining Industry - Brnjak, Hennah Louise Shiner (Curtin University, 2023)
This research ascertains whether a single-objective optimisation model can be successfully employed to assist in managing safety risks in the West Australian metalliferous underground mining industry. The research encompasses the development and commensurate use of a quadratic programming model which was run through IBM CPLEX software. The model ultimately recommends the combination of control measures necessary to be implemented in order to achieve the optimal risk-reduction per dollar invested in safety-risk mitigation.